Pengembangan Flash card Bergambar berbasis Media Konkret untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPAS Materi Rumah Adat di Indonesia Kelas V Sekolah Dasar - Citra, Deswita; Bektiningsih, Kurniana (Universitas Muhammadiyah Magelang, 2026)
This study aims to design, test the feasibility, and determine the effectiveness of using concrete media-based picture cards in improving the learning outcomes of fifth-grade students at SD Negeri 2 Ngabean in the subject of IPAS with the topic of Traditional Houses in Indonesia. The research method used is research and development (R&D). Data collection was carried out through observation, interviews, and learning outcome tests in the form of pre-tests and post-tests. Data analysis used descriptive quantitative analysis techniques to test the feasibility of the media and statistical tests in the form of Paired Sample T-Tests and N-Gain Scores to see the increase in learning outcomes. The results showed that the flash cards developed were considered very feasible to use based on expert validation. The effectiveness test results showed a significant increase in learning outcomes, with an average pre-test score of 45.14% increasing to 81.64% on the post-test. Based on the N-Gain Score calculation, the improvement found falls into the effective category for optimizing student understanding. The development of concrete media-based picture flash cards proved to be effective in improving IPAS learning outcomes in the subject of Traditional Houses in Indonesia in grade V at SD Negeri 2 Ngabean.